Exploration of Serum Exosomal LncRNA TBILA and AGAP2-AS1 as Promising Biomarkers for Diagnosis of Non-Small Cell Lung Cancer - Tao, Yao (Int J Biol Sci, 2020)
Non-small cell lung cancer is the most common type of cancer with a poor prognosis, and development of an effective diagnostic method is urgently needed. Exosomal lncRNAs, a class of transcripts longer than 200 nucleotides packaged into exosomes, have been defined as an ideal diagnostic biomarker for cancer. However, little is known about the clinical utility of exosomal lncRNAs in NSCLC. Here, we aimed to identify exosomal lncRNAs as promising biomarkers for NSCLC diagnosis. First, serum exosomes from NSCLC patients were successfully isolated by a polymer precipitation kit and then identified by TEM, NTA and western blot analysis. A total of nine candidate lncRNAs were detected by qRT-PCR in a training set. The two exosomal lncRNA TBILA and AGAP2-AS1 were screened out for the higher levels in NSCLC patients than that of healthy controls in a validation set. And there was a significant positive correlation between these exosomal lncRNAs levels and tumor size, lymph node metastasis and TNM stage. Additionally, we validated that these exosomal lncRNAs were stable in serum. Next, we evaluated the diagnostic efficiency of exosomal lncRNAs in NSCLC patients by ROC curve analysis. The data showed that individual TBILA or AGAP2-AS1 exhibited better diagnostic efficiency in NSCLC patients with different tumor pathologic subtypes and early stage, whereas the combination of lncRNAs did not provide better results than individual lncRNAs. Notably, the combination of two exosomal lncRNAs and the serum tumor biomarker Cyfra21-1 widely used in clinical practices further improved the diagnostic accuracy for NSCLC patients. This study suggests that exosomal lncRNA TBILA and AGAP2-AS1 may be promising biomarkers for diagnosis of NSCLC.